Neuroendocrine tumors of the digestive system: pathologic and molecular characteristics - V. V. Delektorskaya (Успехи молекулярной онкологии)
This review deals with the analysis of up-to-date concepts of the human neuroendocrine tumors (NETs) of the digestive system, which are a heterogeneous group of epithelial neoplasms arising from the diffuse neuroendocrine system of the gastrointestinal tract and pancreas. The review summarizes the information about the specifics of the recent histological classifications and criteria of diagnosis the different types of neuroendocrine neoplasms accounting histological and immunohistochemical parameters. In the light of these criteria, current issues of the nomenclature, as well as systems of grading and staging are discussed. Well-differentiated NETs generally present characteristic histopathological features with nests, trabecular or gland-like formations, low mitotic activity and Ki-67 labeling indices and are mostly classified as either G1 or G2 NET. In contrast, poorly differentiated neuroendocrine carcinomas have diffuse growth pattern, high-grade nuclear atypia and cellular proliferation, necrosis. They are always classified as G3 and further subclassified into small-cell or large-cell types based on their histological features. Immunohistochemistry is a powerful tool in confirming neuroendocrine differentiation of tumor cells by the expression of chromogranin A and/or synaptophysin. The grade (G) is based on the proliferative activity of the tumor assessed by the mitotic rate or by Ki-67 immunohistochemistry. Several markers are useful in the identification of a primary organ of NETs in metastatic lesions are also discussed. NETs represent challenging neoplasms in terms of clinical management and prognosis assessment. Morphology alone and immunophenotypic features have no specific predictive implications. Ki-67 has been proven the only significant prognostic marker and can predict response to therapy. Additionally, data on key signaling pathways and potential predictive molecular markers involved in the development of neuroendocrine tumors of the gastrointestinal tract and pancreas are presented in this review. New molecular targeted therapies have become available in patients with NETs. Somatostatin receptors (SSTRs) are expressed by these tumors and show high affinity for somatostatin analogues. Immunohistochemical positive staining, especially of the subtype SSTR 2А, has been shown to be well associated with therapeutic response to somatostatin analogue therapy. Detecting the expression of SSTRs helps to predict not only the efficacy of treatment but also the prognosis in NETs. The PI3K/AKT/mTOR signaling pathway plays a crucial role in development of neuroendocrine neoplasms and is targeted by specific inhibitors. However, the exact cellular molecules, which may help predict response, their expression levels and prognostic values are still to be defined. Determining specific prognostic and predictive molecular markers in NETs can significantly improve biological and morphological characterization of individual neuroendocrine neoplasms and identification of patients that may benefit from targeted therapy.